Developmental Plasticity in Child Growth and Maturation - Hochberg, Ze'ev (Frontiers in Endocrinology, 2011)
The ability of a given genotype to produce different phenotypes in response to different environments is termed "plasticity", and is part of the organism's "adaptability" to environmental cues. The expressions of suites of genes, particularly during development or life-history transitions, probably underlie the fundamental plasticity of an organism. Plasticity in developmental programming has evolved in order to provide the best chances of survival and reproductive success to organisms under changing environments. Environmental conditions that are experienced in early life can profoundly influence human biology, child growth and maturation, and long-term health and longevity. Developmental origins of health and disease and life history transitions are purported to use placental, nutritional, and endocrine cues for setting long-term biological, mental, and behavioral strategies for child growth and maturation in response to local ecological and/or social conditions. The window of developmental plasticity extends from conception to early childhood, and even beyond to the transition from juvenility to adoelscence, and could be transmitted transgenerationally. It involves epigenetic responses to environmental changes, which exert their effects during life history phase-transitions.